Review of the subgenus Xizicus (Xizicus) Gorochov, 1993 (Orthoptera: Tettigoniidae: Meconematinae) from China - Feng, Jiyuan; Shi, Fuming; Mao, Shaoli (Zootaxa, 2017)
Gorochov (1993) erected the subgenus Xizicus (Xizicus), with the type species Xizicus (Xizicus) fascipes (Bey-Bienko, 1955). This subgenus is distinguished from the other subgenera of Xizicus by the following characters: male tenth abdominal tergite with a pair of contiguous posterior processes in the middle; subgenital plate simple, styli slender, located on the apices or subapices of lateral margins; posterior margin of female subgenital plate rounded.